Analisis Fenomena Martial Rape Terhadap Pemenuhan Tujuan Perkawinan - Muhammad Zainuddin Sunarto; Naila Jaliyah (Jurnal Bedah Hukum, 2023)
The occurrence of Marital Rape is due to a person who cannot withstand the turmoil of his passions without thinking about his partner who is still unable to serve because of some things that make him unwilling. This study aims to examine the “Analysis of Marital Rape Phenomena on the fulfillment of marital goals” by using a research methodology Literature study (Library Research) which uses several books, journals, and other literature as the main object to obtain data on Marital Rape. Based on the results of this study, Marital Rape should be avoided by someone who is married, because if the husband commits forced contact with his wife, it will have a bad impact such as hurting the wife either physically or psychically, the wife is afraid, the wife will be traumatized, there will also be less trust and affection of the wife towards the husband. Whereas in marriage there are several fulfillments and goals to be achieved by all couples such as the purpose of carrying out God’s commands and worship, Following the sunnah of Rosul, continuing heredity, and for psychological needs in the fulfillment of one’s sexual gratification needs. If Marital Rapeis performed by men then certainly in the family there will be no more harmony and there will be no achievement of the purpose of the execution of marriage.